2014
DOI: 10.1094/pdis-09-13-0957-re
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Genomics-Based LAMP (Loop-Mediated Isothermal Amplification) Assay for Detection ofPseudomonas fuscovaginaefrom Rice

Abstract: The vast amount of data available through next-generation sequencing technology is facilitating the design of diagnostic marker systems. This study reports the use of draft genome sequences from the bacterial plant pathogen Pseudomonas fuscovaginae, the cause of sheath brown rot of rice, to describe the genetic diversity within a worldwide collection of strains representing the species. Based on a comparative analysis with the draft sequences, primers for a loop-mediated isothermal amplification (LAMP) assay w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 42 publications
2
27
0
Order By: Relevance
“…For molecular-based pathogen diagnose, the selected DNA signatures must be highly specific for the target pathogen to provide reliable detection results. By the continuously increasing amount of genome sequences, new unique targets were screened thorough comparative genomic analysis carried out in silico, and validated using PCR and/or hybridization-based approaches (Mazumder et al 2005;Phillippy et al 2007;Albuquerque et al 2011Albuquerque et al , 2012Bühlmann et al 2013;Ash et al 2014). Although no draft genome sequence of X. axonopodis pv.…”
Section: Discussionmentioning
confidence: 99%
“…For molecular-based pathogen diagnose, the selected DNA signatures must be highly specific for the target pathogen to provide reliable detection results. By the continuously increasing amount of genome sequences, new unique targets were screened thorough comparative genomic analysis carried out in silico, and validated using PCR and/or hybridization-based approaches (Mazumder et al 2005;Phillippy et al 2007;Albuquerque et al 2011Albuquerque et al , 2012Bühlmann et al 2013;Ash et al 2014). Although no draft genome sequence of X. axonopodis pv.…”
Section: Discussionmentioning
confidence: 99%
“…The speed of the LAMP assay was also advantageous, where results were produced within a one hour when compared to the nested PCR technique, which can take 9 hours to complete. The LAMP method is a rapid diagnostic tool for glasshouse and laboratory studies and offers the potential to be applied in the field56. The 16S gene region used in this assay is highly conserved among phytoplasmas and so the design of primers using other gene regions or the use of whole genome sequencing would improve the discriminatory power of the assay.…”
Section: Discussionmentioning
confidence: 99%
“…The LAMP method has further advantages as the polymerase used is not easily affected by DNA amplification inhibitors and that the presence or absence of DNA amplification can be confirmed by turbidity, making electrophoresis unnecessary. Thus, the LAMP method is ideal for conducting rapid disease diagnosis and several previous studies have been reported for the identification of pathogenic viruses (Suzuki et al., ), viroids (Thanarajoo, Kong, Lau, & Vadamalai, ), fungi (Fukuta et al., ) and bacteria (Ash et al., ). The LAMP assay for detecting MEAM1 and MED, which has been reported so far (Dickey, Osborne, Shatters, & Mckenzie, ; Hsieh, Wang, Chen, & Ko, ; Takeuchi, Yoshimura, Fukuta, & Ooya, ), is intended identify each species individually, but are not suitable for simultaneously identifing species in a multiplex analysis.…”
Section: Introductionmentioning
confidence: 99%
“…method is ideal for conducting rapid disease diagnosis and several previous studies have been reported for the identification of pathogenic viruses (Suzuki et al, 2016), viroids (Thanarajoo, Kong, Lau, & Vadamalai, 2014), fungi (Fukuta et al, 2017) and bacteria (Ash et al, 2014). The LAMP assay for detecting MEAM1 and MED, which has been reported so far (Dickey, Osborne, Shatters, & Mckenzie, 2013;Hsieh, Wang, Chen, & Ko, 2012;Takeuchi, Yoshimura, Fukuta, & Ooya, 2010), is intended identify each species individually, but are not suitable for simultaneously identifing species in a multiplex analysis.…”
mentioning
confidence: 99%